Development Of Digital Comic Learning Media Based on Local Wisdom in Pancasila And Citizenship Education Subjects - Alfanda, Noviyasti; Jamaludin, Ujang; Bahrudin, Febrian Alwan (Universitas Tanjungpura, 2024)
Education is an attempt made to facilitate understanding, awareness, and development of knowledge, analytical skills, and effective skills through various learning media. In this research, problems existed in the form of a lack of innovation in the use of learning media and difficulty for students to understand the material. Thus, there was a need for innovative media for learning, like digital comics. However, digital comic media had drawbacks that must be improved through the development stage. Hence, this research aimed to create innovation by developing media for learning in the form of corresponding digital comics. The method used was RD (Research and Development) with Thiagarajan's 4D model, consisting of Define, Design, Development, and Dissemination. The findings showed: